Rice root properties for internal aeration and efficient nutrient acquisition in submerged soil - Kirk, Guy J D (The New phytologist, 2003)
•  The characteristics of Oryza sativa roots required for internal aeration may conflict with those for efficient nutrient acquisition, particularly the surface area available for absorbing nutrients and the extent of oxygenation of the rhizosphere. •  A model was developed for calculating the steady-state diffusion of O2 through a primary root and its laterals and the simultaneous consumption of O2 in respiration and loss to the soil. Results for a realistic set of parameter values were compared with available experimental data, and a sensitivity analysis given. •  It was seen that a system of coarse, aerenchmymatous, primary roots with gas-impermeable walls conducting O2 to short, fine, gas-permeable laterals (i.e. the basic architecture of current rice genotypes) provided the greatest absorbing surface per unit aerated root mass. •  With this architecture and typical rates of root respiration, rates of O2 loss to the soil can be sufficient to, for example, nitrify sufficient NH4 + to NO3 - to allow a plant to absorb half its N as NO3 - , as well as to oxidize toxins such as Fe2+